Hannah Arendt and the Specter of Totalitarianism - LaFay, Marilyn; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2014)
This work positions Arendt as a political writer attempting to find a way in which humanity, poised between the Holocaust and the atom bomb, might reclaim its position as the creators of a world fit for human habitation.
Keywords: Philosophy; Political science; Political theory; World politics; Political philosophy; Social sciences -- Philosophy; Movement (Philosophy).; Political Philosophy; Social Philosophy; Philosophical Traditions; Political History